Classification of Mental Disorders Using Modified Balanced Random Forest And Feature Selection - Arsad; Alva Hendi Muhammad; Tonny Hidayat (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
This study employs the Modified Balanced Random Forest (MBRF) algorithm and Correlation-based Feature Selector (CfsSubsetEval) for mental disorder classification. The